2012
DOI: 10.7135/upo9781843313441
|View full text |Cite
|
Sign up to set email alerts
|

Overseas Chinese Christian Entrepreneurs in Modern China

Abstract: Inspired by Max Weber’s thesis on the Protestant ethic, this volume examines the influence of Christianity on overseas Chinese entrepreneurs working in China during its transition from a centrally-planned economy toward a market economy under Communist rule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Meanwhile, for the business leaders, a Christian corporate culture is highly conducive for sustaining Christian witness. In a study by Tong (2012) on overseas Chinese Christian businesspeople in Shanghai, personal piety was found serve as the foundation of business ethics and guide their dealings with Chinese officials, clients, business partners, and ordinary workers. In their study on trust among Protestant entrepreneurs, Tong and Yang (2016) found that Chinese Protestant entrepreneurs wanted to be more trustworthy and to be more trustful of others, after becoming Christians, and some of them thought that a major religion like Christianity would lead to better moral behavior.…”
Section: Spirituality and Religion In The Workplace: An Overviewmentioning
confidence: 99%
“…Meanwhile, for the business leaders, a Christian corporate culture is highly conducive for sustaining Christian witness. In a study by Tong (2012) on overseas Chinese Christian businesspeople in Shanghai, personal piety was found serve as the foundation of business ethics and guide their dealings with Chinese officials, clients, business partners, and ordinary workers. In their study on trust among Protestant entrepreneurs, Tong and Yang (2016) found that Chinese Protestant entrepreneurs wanted to be more trustworthy and to be more trustful of others, after becoming Christians, and some of them thought that a major religion like Christianity would lead to better moral behavior.…”
Section: Spirituality and Religion In The Workplace: An Overviewmentioning
confidence: 99%
“…King (: 76–8) goes on to indicate the numerous ways in which guanxi avoidance might be achieved (see also Hwang, : 964–67). More recently there has been reported guanxi avoidance practiced by Christian businessmen and women in China (Tong, ). Distaste for guanxi is frequently expressed by mainland Chinese citizens precisely because it is particularistic, applied – if not designed – to circumvent rules and procedures, and because of its possible association with corruption.…”
Section: The Efficiency Of Guanximentioning
confidence: 99%